(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The article deals with modelling of two-dimensional financial data set using Weibull distribution extended to two-dimensional setting. The generalization in two dimensions is not direct, it goes through representation of one-dimensional asymmetric Laplace distribution. The characteristics of the new distribution are described, and parameters are estimated using the method of moments. Statistical package R is used to perform numerical search. At the end, the application of this new two- dimensional family of distributions is discussed.